The Atlantic Meridional Overturning Circulation as productivity regulator of the North Atlantic Subtropical Gyre. Issue 1 (14th November 2018) - Nave, Sílvia; Lebreiro, Susana; Michel, Elisabeth; Kissel, Catherine; Figueiredo, Maria Ondina; Guihou, Abel; Ferreira, António; Labeyrie, Laurent; Alberto, Ana
Abstract: Spatially extensive and intense phytoplankton blooms observed off Iberia, in satellite pictures, are driven by significant nutrient supply by upper-ocean vertical mesoscale activity rather than by horizontal advection by coastal upwelling. Productivity of oligotrophic regions is still poorly depicted by discrete instrumental and model data sets. The paleoproductivity reconstructions of these areas represent the mean productivity over long periods, bringing new insights into the total biomass fluxes. Here, we present paleoproductivity records from the oceanic Tore Seamount region, covering the period from 140 to 60 ka. They show higher nutrient supplies during Termination II, Marine Oxygen Isotope Stage (MIS) 4, MIS 6, and warming transitions of the MIS 5 sub-stages. The highest nutrient content (higher productivity) in phase with tracers of bottom-water ventilation (benthic δ 13 C, 231 Pa/ 230 Th) establishes a strong linkage with variability of Southern Ocean-sourced waters. Low productivity and ventilation over warm sub-stages of MIS 5 respond instead to North Atlantic Deep Water. Assuming that the Tore Seamount is representative of oligotrophic regions, the glacial-interglacial relationship observed between paleoproductivity and Atlantic Meridional Overturning Circulation strength opens new insights into the importance of estimating the total biomass in these regions. The subtropical gyres might play a considerable role in the carbon cycle over (sub-)glacial-interglacial time scales than previously thought.